Learning Interest and Its Role in Students’ Grammar Acquisition - Dian Agustina Purwanto Wakerkwa; Novi Indriyani (Journal on Education, 2023)
Grammar is central in language learning and acquisition. Learning a foreign language means learning how the sentences are correctly formed and function. In that process, several skills are required to learn with no exception the knowledge of grammar. In addition to that, having an adequate amount of interest can influence the grammar learning outcome. With that consideration, this study aimed to examine the knowledge of simple tenses of fourteen first-year English Education students in one of Indonesia universities and to investigate whether their learning interests have a significant role in their performance. The data were collected through observation, a test, and a close-ended interview, and were analyzed through a descriptive quantitative method. The results of the test show that students’ grammar competence was inadequate. Several factors were identified as the causes for such findings. However, they showed a great interest in learning the language which can be a starting point for future improvement.